Perivascular Epithelial Cell Tumor of the Stomach Diagnosed Preoperatively by Endoscopic Ultrasound-Guided Fine-Needle Aspiration - Wang, Limei; Zhang, Jing (Current Medical Imaging, 2024)
Introduction Perivascular Epithelioid Cell tumor (PEComa) is a rare mesenchymal neoplasm characterized by the co-expression of melanocytic and myoid markers. While PEComas can arise in diverse anatomical sites, gastric PEComas are exceedingly rare, with merely nine cases documented in the extant literature. Case Presentation Herein, we have presented a case of gastric PEComa in a 65-year-old male patient who exhibited a 3-year history of epigastric pain, with notable exacerbation in the two months prior to diagnosis. For the initial evaluation of the patient's condition, Endoscopic Ultrasound-guided Fine Needle Aspiration (EUS-FNA) and Computed Tomography (CT) were employed, which enabled a preoperative diagnosis. Radiological assessment demonstrated a neoplasm exhibiting heterogeneous arterial enhancement, persistent delayed enhancement, and distinct margins. Subsequent to diagnosis, the patient underwent surgical resection and has maintained a disease-free status for one year postoperatively. This case report highlights the crucial role of EUS-FNA in facilitating preoperative histological diagnosis and optimizing surgical planning for gastric PEComa. Conclusion This case constitutes the tenth documented instance of gastric PEComa in the global literature. In this case, EUS-FNA facilitated a preoperative histopathological diagnosis, thereby enabling precise surgical planning. An accurate preoperative diagnosis is crucial for devising an optimal treatment strategy.
Keywords: Computed tomography